Minimally Invasive Platforms in Biosensing - Pandey, P.C.; Pandey, G.; Narayan, R.J. (Frontiers Media S.A., 2020)
The interaction of sensing components with body fluids is a basic requirement for clinical diagnostics; a variety of novel platforms have recently been developed for invasive and non-invasive sensing. In this manuscript, recent advancements related to minimally invasive platform for biosensing are reviewed. Many approaches have been utilized for generating minimally invasive platforms that require a small volume of body fluid; for example, the use of small-scale needles known as microneedles for minimally invasive detection has been demonstrated. The use of capillary action in microneedle-assisted biosensing may facilitate the detection of analytes in body fluids. This review considers recent innovations in the structure and performance of minimally invasive sensos. © Copyright © 2020 Pandey, Pandey and Narayan.
Keywords: transdermal biosensing; microfabrication; microfluidics; microneedle; luminescent sensors; fluorescent biosensors